Effect of modified atmosphere on phytochemical profile of pasteurized peach purées - Oliveira, Ana (2016)
Peach phytochemical profile was analysed during 90 days storage under three different gas mixtures: 10 kPa O2+90 kPa N2, 100 kPa N2 and air (78 kPa N2+21 kPa O2+0.03 kPa CO2) for both 4 and 23 °C. The antioxidant activity increased when peach purée was stored under air at 4 °C and 100 kPa N2 at 23 °C, while total phenolic content was not affected by atmospheres. Total carotenoids were more stable for 100 kPa N2, where it decreases 48 and 58% respectively for 4 and 23 °C. The content of (+)-catechin decreased 42% for 10 kPa O2 at 4°C, remaining constant in other atmospheres. Chlorogenic and neochlorogenic acids were well preserved in atmospheres containing oxygen, presenting an increase of 14 and 24% for 10 kPa O2 at 4°C. The higher content of carotenoids was obtained for 100 kPa N2 at 23 °C. Principal component analysis shows that atmospheres variance was associated with carotenoids while storage time was more related with total phenolics and total antioxidant capacity.